Physical model tests and numerical simulation for assessing the stability of brick-lined tunnels - Chen, Han-Mei; Yu, Hai-Sui; Smith, Martin J. (Elsevier, 2016)
Nowadays, numerical modelling is increasingly used to assess the stability of tunnels and underground caverns. However, an analysis of the mechanical behaviour of existing brick-lined tunnels remains challenging due to the complex material components. In order to study the mechanical behaviour of the masonry in brick-lined tunnels, this paper reports a series of small scale physical tunnel model tests to represent the true behaviour of a real tunnel under extreme loading. Advanced monitoring techniques of laser scanning and photogrammetry are used to record tunnel deformation and lining defects. This investigation shows how these techniques may substitute or supplement the conventional monitoring procedures. Moreover, numerical analyses based on continuum and discontinuum approaches are carried out. The numerical results are compared with physical model tests to assess the overall stability of these tunnels. Predictions using numerical models under various conditions have also been carried out to show the mechanical behaviour of masonry tunnel and to quantify the influence of the boundary and loading conditions.